Penatalaksanaan Fisioterapi Kasus Carpal Tunnel Syndrome Billateral: Case Report - Rizki Nisaa’Ul Janah; Rosella Komalasari; Munawar Munawar (Journal of Educational Innovation and Public Health, 2026)
Introduction: Carpal Tunnel Syndrome (CTS) is the most common neuropathy caused by compression and tension of the median nerve in the carpal tunnel of the wrist. The most common symptoms of CTS include pain and paresthesia (tingling) with or without numbness in the me dian nerve area of ​​the wrist. Method: The method used was a case study on a 72-year-old male patient diagnosed with bilateral CTS who experienced pain (NRS 7/10), tingling, numbness, and limitations in hand movement and functional activity. Physiotherapy interventions provided included Ultrasound therapy (US), Transcutaneous Electrical Nerve Stimulation (TENS), nerve mobilization, and structured exercise therapy in the form of stretching and median nerve gliding. Evaluation was carried out using the Numeric Rating Scale (NRS) for pain and the Boston Carpal Tunnel Questionnaire (BCTQ) for functional activity. Result: The results showed a significant reduction in pain, with motion pain decreasing from a scale of 7 to 3 and pressure pain from 5 to 1 after three therapy sessions. Furthermore, there was an increase in functional activity, as indicated by a decrease in BCTQ scores, namely the Symptom Severity Scale (SSS) from 4 to 2 and the Functional Status Scale (FSS) from 4 to 2. This indicates a gradual improvement from the moderate-severe category to approaching mild. Conclusion: A multimodal physiotherapy approach is effective in reducing pain, reducing paresthesias, and improving hand function in CTS patients. Combining various therapeutic modalities has been shown to be more optimal than single therapies because it can address various pathological aspects simultaneously. Therefore, comprehensive, evidence-based physiotherapy interventions are highly recommended in the conservative management of CTS.